Thermally assisted interlayer magnetic coupling through Ba0.05Sr0.95TiO3 barriers - Carreira, Santiago José (2016)
We report on the interlayer exchange coupling across insulating barriers observed on Ni80Fe20/Ba0.05Sr0.95TiO3/La0.66Sr0.33MnO3 (Py/BST0.05/LSMO) trilayers. The coupling mechanism has been analyzed in terms of the barrier thickness, samples' substrate, and temperature. We examined the effect of MgO (MGO) and SrTiO3 (STO) (001) single-crystalline substrates on the magnetic coupling and also on the magnetic anisotropies of the samples in order to get a deeper understanding of the magnetism of the structures. We measured a weak coupling mediated by spin-dependent tunneling phenomena whose sign and strength depend on barrier thickness and substrate. An antiferromagnetic (AF) exchange prevails for most of the samples and smoothly increases with the barrier thicknesses as a consequence of the screening effects of the BST0.05. The coupling monotonically increases with temperature in all the samples and this behavior is attributed to thermally assisted mechanisms. The magnetic anisotropy of both magnetic components has a cubic symmetry that in the case of permalloy is added to a small uniaxial component.